Post-consumption foamed polystyrene coatings for surface tension modification. (July 2020) - Bustos, N; Gamarra, C; Ponton, D; Roa, M
Abstract: Foamed polystyrene, commercially known as Icopor, occupies a very important place in the transport systems, and conservation of freight and food, but it is also one of the main polymeric pollutants, due to its low biodegradability, and low reuse. Polystyrene has in its structure aromatic and aliphatic functional groups, which have a high hydrophobicity, which makes them candidates as modifiers of permeability and surface properties, although for this purpose the implementation of solvents is also required. In the following work, polystyrene residues for domestic and food use were used to obtain coatings, which allow surface tension to be modified, on surfaces with high water permeability. For this purpose, the polymeric residue was dissolved in organic type solvents, generating a varnish, which was used to coat the study surface, from which the surface tension with respect to water was previously known by analysing the contact angle; to be compared with those obtained after coating, resulting in an increase in the contact angle, which indicates an increase in surface tension, conferred on the new surface hydrophobicity.